Uma diferente perspectiva de igualdade: breve investigação da ótica conservadora de Thomas Sowell sobre questões disputadas de Igualdade - Demirdjian, Marcelo Bonotto (2020)
This dissertation seeks to carry out in the field of the zetetic approach an investigation about the conservative view of equality from the perspective of Thomas Sowell. Through a qualitative bibliographic and documentary research, we seek to answer the simplistic question: “how does Thomas Sowell see the principle of equality?”. Therefore, we initially seek to define the historical context of the conservative political vision with a focus on its reflexes in the United States from its roots as a tradition to its definition as a modern political movement. In a second moment, Thomas Sowell's position in this modern political current is established, especially in relation to the theoretical conflict proposed by the author for the understanding of the world, the restricted and unrestricted views, where the very concept of equality is understood in different ways. Finally, we analyze the practical consequences of these views of equality defined by Thomas Sowell on issues outlined by him as conflicting, involving political practice.